Modulation of expression of the sigma receptors in the heart of rat and mouse in normal and pathological conditions - Novakova, M; Bruderova, V; Sulova, Z; Kopacek, J; Lacinova, L; Kvetnansky, R; Vasku, A; Kaplan, P; Krizanova, O; Jurkovicova, D (General physiology and biophysics, 2007)
The aim of the present work was to study the effect of various stressors (hypoxia, cold, immobilization) on the gene expression of sigma receptors in the left ventricles of rat heart. We have clearly shown that gene expression of sigma receptors is upregulated by strong stress stimuli, such as immobilization and/or hypoxia. Nevertheless, cold as a milder stressor has no effect on sigma receptor's mRNA levels. Signalling cascade of sigma receptors is dependent on IP(3) receptors, since silencing of both, type 1 and 2 IP(3) receptors resulted in decreased mRNA levels of sigma receptors. Physiological relevance of sigma receptors in the heart is not clear yet. Nevertheless, based on the already published data we can assume that sigma receptors might participate in contractile responses in cardiomyocytes.
Keywords: kultivované buňky; messenger RNA; terapeutická hypotermie; Rats; hypoxie; Hypoxia; Receptors, sigma; inositol-1,4,5-trisfosfát - receptory; potkani Sprague-Dawley; receptory sigma; RNA interference; Inositol 1,4,5-Trisphosphate Receptors; Gene Expression Regulation; Stress, Physiological; mužské pohlaví; potkani inbrední SHR; Immobilization; Mice; RNA Interference; srdeční komory; Hypothermia, Induced; fyziologický stres; Mice, Inbred Strains; inbrední kmeny myší; Myocytes, Cardiac; krysa rodu Rattus; regulace genové exprese; věkové faktory; Cells, Cultured; RNA, Messenger; zvířata; imobilizace; Heart Ventricles; Rats, Inbred WKY; myši; Rats, Sprague-Dawley; Age Factors; kardiomyocyty; Rats, Inbred SHR; potkani inbrední WKY; Male; Animals